1985
DOI: 10.2527/jas1985.613590x
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Dietary Selenium Levels on Blood Levels of Selenium and Glutathione Peroxidase Activity in the Horse

Abstract: Twenty mature geldings, averaging 535 kg, were used to determine the influence of dietary selenium (Se) on the blood levels of Se and Se-dependent glutathione peroxidase (SeGSH-Px) activity in the horse. Horses were randomly assigned within breed to four treatments consisting of five horses each and fed a basal diet containing .06 ppm of naturally occurring Se. Diets were supplemented with .05, .10 and .20 ppm Se, as sodium selenite. Blood was drawn for 2 wk before, and for 12 wk following, the inclusion of su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
4
2
8

Year Published

1995
1995
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 12 publications
8
4
2
8
Order By: Relevance
“…This finding agrees with previous studies where no differences in the P GPx-3 activity were reported in Se-deficient humans or rats after consuming different sources of supplemental Se (Levander et al, 1983;Deagen et al, 1987). The lack of effect due to Se supplementation on P GPx-3 is similar to previous reports where P GPx-3 activity of horses did not respond to 12 wk of supplementation, even when plasma Se concentration showed an increase (Shellow et al, 1985). Fluctuating P GPx-3 activity, similar to that in the current study, was reported for horses fed Se-adequate diets by Podoll et al (1992).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This finding agrees with previous studies where no differences in the P GPx-3 activity were reported in Se-deficient humans or rats after consuming different sources of supplemental Se (Levander et al, 1983;Deagen et al, 1987). The lack of effect due to Se supplementation on P GPx-3 is similar to previous reports where P GPx-3 activity of horses did not respond to 12 wk of supplementation, even when plasma Se concentration showed an increase (Shellow et al, 1985). Fluctuating P GPx-3 activity, similar to that in the current study, was reported for horses fed Se-adequate diets by Podoll et al (1992).…”
Section: Discussionsupporting
confidence: 92%
“…Plasma Se concentrations of horses in the current study responded to supplementation over a relatively short time, having plateaued by d 28. This finding is similar to Shellow et al (1985), who reported that plasma Se concentrations of supplemented horses were greater than nonsupplemented horses after 2 wk of supplementation. It is worth noting that even though the CTRL diet provided 1.5 times the estimated requirement (NRC, 1989), the plasma Se concentrations of these horses were approximately 0.1 g/mL, compared with 0.14 g/mL previously reported by Shellow et al (1985) for horses receiving a similar amount of dietary Se.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…2). Wenn in den Untersuchungen von Shellow et al(1985) nach Se-Zulagen keine positive Reaktion gefunden wurde, so kann das an der bereits in der Kontrollperiode hohen GSH-Px-Aktivität gelegen haben, da nur bei zuvor marginaler Versorgung eine deutliche Anderung zu erwarten ist. Aufgrund vorgenannter Beziehungen dürften die Differenzen in der Plasma-GSH-Px-Aktivität zwischen Sommerund \ü/interhalbjahr auf Unterschieden in der Se-Aufnahme beruhen, da im Winter z. T. Misch-und Mineralfutter eingesetzt wurden, die im allgemeinen mit Selen supplementiert sind.…”
Section: Introductionunclassified